Analysis of Smart Grid security standards - Yong Wang; Da Ruan; Dawu Gu; Gao, Jason; Daming Liu; Jianping Xu; Fang Chen; Fei Dai; Jinshi Yang (2011 IEEE International Conference on Computer Science and Automation Engineering, 2011)
Smart Grid security is very important subject. Vulnerabilities from cyber, smart meter, zone management, protection procedures and security assessment will make Smart Gird risk. IEC Smart Grid Standardization, IEEE Power & Energy Society (PES), National Institute of Standards and Technology (NIST) and National Standard of People's Republic of China are developing the corresponding security standards for Smart Grid. In this paper, we summarized Smart Grid security key standards NIST Inter agency Report 7628, IEC 61850 & GB/T22239 security classified protection standards, IEC 62351 on Smart Grid security, ISO/IEC 15408 & GB18336 security assessment standards and ISO 27001& GB/T22080 information security management standards. We summarized the security technology in Smart Grid which the international organization are developing the corresponding standards. State Grid Corporation of China (SGCC) has begun to develop standards on the IEC in UHV power transmission, high/ultra high voltage direct current transmission aspects.